EFFICACY OF H1 ANTIHISTAMINES IN CHILDREN WITH FOOD ALLERGY - I.I. Balabolkin; L.D. Ksenzova; L.A. Razina; O.B. Sosnina; V.S. Reutova; E.A. Tsvetkova (Вопросы современной педиатрии, 2007)
The authors assesed a clinical efficacy of Zirtek (cetirizin) in 27 children with atopic dermatitis and 40 children with bronchial asthma, associated with food sensitization. Positive therapeutic effect was achieved in 92,5% patients with atopic dermatitis and 87,5% children with bronchial asthma. The improvement of lung functions, decreasing bronchial hyperrecactivity in children with bronchial asthma and of itch and skin`s inflammation in patients with atopic dermatitis are achieved.Key words: food allergy, h1 antihistamines, cetirizine.